Hope and challenges in the diagnosis and treatment of Wilms tumor: a single-center retrospective study in China - Cui, Kongkong; Hong, Peng; Lin, Jie; Hu, Zaihong; Gao, Zhiqiang; Tian, XiaoMao; Lin, Tao; Shi, Qinlin; Wei, Guanghui (Frontiers in Pediatrics, 2025)
BackgroundWilms tumor (WT), which represents about 90% of kidney tumors in children, is the most prevalent type of renal tumor among children. In developed countries, advancements in treatments such as chemotherapy and radiotherapy have led to high survival rates. However, developing countries face significant challenges, including late-stage diagnosis, metastasis at presentation, and high rates of treatment abandonment.MethodsThis retrospective study included all patients diagnosed with WT at a tertiary hospital in Western China from 2007 to 2021. It involved the collection of sociodemographic and clinical details, including data on patients who abandoned treatment. Follow-up continued until July 2024.ResultsThis study consisted of 301 WT patients. Of the 259 who completed the treatment, the 5-year event-free survival (EFS) and overall survival (OS) rates were 77.9% and 81.2%. Of the 42 patients who abandoned treatment, 13 refused further care immediately after diagnosis and signed a refusal document, 16 discontinued treatments during preoperative neoadjuvant chemotherapy, and 13 failed to complete the prescribed chemotherapy or radiotherapy.ConclusionSurvival rates for WT patients at our institution approach those reported in developed countries. Challenges include late-stage diagnosis, metastasis at initial presentation, and treatment abandonment. To address these issues, implementing pediatric screening is critical for early detection and timely intervention, particularly for families vulnerable to abandoning treatment. For high-risk cases, oncologists need develop targeted strategies to enhance clinical outcomes.